Analisis Nilai-Nilai Pendidikan Islam Dalam Tradisi Upacara Selamatan Kematian Nyewu Dusun Randegan Kutorejo Mojokerto - Amru Almutasim (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
A culture in it always contains the teachings of how life should be lived and leads people to life in accordance with the will of God as the owner and the ruler of nature. One of them is the tradition of nyewu selamatan ceremony. The meaning of the ceremony in this theme leads to the chronologization of the nyewu salvation ritual. Selamatan comes from the word congratulations, the Javanese people use it as a medium to offer prayers for the salvation of the dead and the left. From result of data analysis known that; (1) The history and background of Nyewu tradition implementation in Randegan Kutorejo Mojokerto is the belief that the soul of the dead still roam around his residence, so it needs to be salvation. (2) The values ​​contained in nyewu salvation in Randegan Kutorejo Mojokerto are among others moral values ​​against the deceased, the value of faith, sodaqoh values, the values ​​of ukhuwah Islamiyah and solidarity and the value of help. (3) The influence of Islamic values ​​contained in the Nyewu tradition against religious behavior, does not occur comprehensively in the Randegan community but affects certain circles who have a strong religious soul and awareness.